Effect of Exercise Prescription Implementation Rate on Cardiovascular Events - Zhu, Li-Yue; Li, Min-Yan; Li, Kun-Hui; Yang, Xiao; Yang, Yi-Yong; Zhao, Xiao-Xia; Yan, Ting; Li, Meng-Meng; Luo, Si-Qi; Zhang, Mu-Lan; Su, Jin-Zi (Frontiers in Cardiovascular Medicine, 2022)
Background Exercise prescription of cardiac rehabilitation (CR) is vital in patients with cardiovascular diseases (CVDs) and those carrying high risk for CVDs. However, the relation between the implementation rate of exercise prescription and cardiovascular events (CVEs) is unclear. Design and Methods In this retrospective study, using the administration data from the Rehabilitation Center in a hospital, patients aged ≥18 years with CVDs were consecutively enrolled from November 2018 to May 2021. Patients were divided into the high execution group (HEG) and low execution group (LEG) depending on whether they completed more than half the time of the exercise prescriptions. Baseline characteristics, ultrasonic cardiogram, cardiopulmonary exercise test, follow-up data, and CVEs were collected. Results The mean age of the 197 CR patients was 61.8 ± 13.7 years and the mean follow-up duration was 10.9 ± 4.2 months. Among them, 15 patients suffered CVEs: 4 in the HEG and 11 in the LEG. The incidence of CVEs showed significant differences between HEG and LEG (chi-square test). Free-event survival analysis using Kaplan–Meier survival plots showed that patients in LEG had poor survival. Cox proportional hazards regression analysis revealed that the prescription implementation rate was an independent predictor of CVEs. Conclusions Our study suggested a significant effect of exercise prescription execution rate on the occurrence of CVEs. Further, the HEG of exercise prescription was associated with lower CVDs.